Limitations and modifications in the clinical application of calcium sulfate - Lun, Deng-xing; Li, Si-ying; Li, Nian-nian; Mou, Le-ming; Li, Hui-quan; Zhu, Wan-ping; Li, Hong-fei; Hu, Yong-cheng (Frontiers in Surgery, 2024)
Calcium sulfate and calcium sulfate-based biomaterials have been widely used in nonload-bearing bone defects for hundreds of years due to their superior biocompatibility, biodegradability and nontoxicity. However, lower compressive strength and rapid degradation rate are the main limitations in clinical applications. Excessive absorption causes a sharp increase in sulfate ion and calcium ion concentrations around the bone defect site, resulting in delayed wound healing and hypercalcemia. In addition, the space between calcium sulfate and the host bone, resulting from excessively rapid absorption, has adverse effects on bone healing or fusion techniques. This issue has been recognized and addressed. The lack of sufficient mechanical strength makes it challenging to use calcium sulfate and calcium sulfate-based biomaterials in load-bearing areas. To overcome these defects, the introduction of various inorganic additives, such as calcium carbonate, calcium phosphate, and calcium silicate, into calcium sulfate is an effective measure. Inorganic materials with different physical and chemical properties can greatly improve the properties of calcium sulfate composites. For example, the hydrolysis products of calcium carbonate are alkaline substances that can buffer the acidic environment caused by the degradation of calcium sulfate; calcium phosphate has poor degradation, which can effectively avoid the excessive absorption of calcium sulfate; and calcium silicate can promote the compressive strength and stimulate new bone formation. The purpose of this review is to review the poor properties of calcium sulfate and its complications in clinical application and to explore the effect of various inorganic additives on the physicochemical properties and biological properties of calcium sulfate (Figure 1).